Perpetuation and host range of Alternaria alternata causing brown spot disease of tobacco - and S.S. SREENIVAS, K. KARUNAKARA MURTHY, M.M. SHENOI (Indian Phytopathology, 2003)
Among the two crop residues in soil, infected tobacco stubble was found to be better source for survival than dried infected leaf trash, for Alternaria alternata, the causal pathogen of brown spot of FCV tobacco crop. The pathogen survived for longer period when stored in laboratory than field conditions. Extent of conidial production of the pathogen surviving in these crop residues also followed similar pattern. Though a gradual decrease in perpetuation of the pathogen is noticed, it survived in crop residues for a longer period, enough to provide sufficient primary inoculum for new crop in the following season. Host range studies confirmed common weeds around tobacco field, viz., Cassia occidentalis, Crotalaria calycina, C. mucronata, Cyperus spp., Euphorbia pulcherrima and Trianthema decandra as collateral hosts. The comprehensive brown spot management schedule recommended for the farming community includes steps to eliminate these two important sources of inoculum.